2-D Grating Couplers for Vertical Fiber Coupling in Two Polarizations - Tatsuhiko Watanabe; Yuriy Fedoryshyn; Juerg Leuthold (IEEE Photonics Journal)
We demonstrate highly efficient couplers in a two-dimensional grating configuration for a vertical fiber-coupling fabricated in the silicon-on-insulator platform. A combination of sub-wavelength reflectors and blazed gratings enables both high coupling efficiency and vertical grating coupling. We experimentally achieve coupling efficiencies of −2.6 dB at 1544 nm and −3.4 dB at 1536 nm for x- and y-polarized LP01 modes, respectively. The experimental results are in good agreement with the simulated −2.4 dB coupling efficiency for both polarizations at a wavelength of 1550 nm. Simulated and measured crosstalk between two polarizations were −19 dB and <−16 dB, respectively.